The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.macromol.2c01273
|View full text |Cite
|
Sign up to set email alerts
|

Living Crystallization-Driven Self-Assembly of Linear and V-Shaped Oligo(p-phenylene ethynylene)-Containing Block Copolymers: Architecture Effect of π-Conjugated Crystalline Segment

Abstract: Diblock copolymers (BCPs) with a π-conjugated block and an appropriate block ratio can undergo crystallizationdriven self-assembly (CDSA) to form fiber-like micelles of uniform width and length. Almost all examples in the literature involve BCPs with a linear π-conjugated block. We are interested in exploring the influence of the architecture of the π-conjugated block on (living) CDSA of oligo(p-phenylene ethynylene) (OPE) BCPs with a common block length and the same corona-forming block. Herein, we designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…The length of the resulting comicelles appeared to increase linearly with n unimer / n seed , which was shown in our previous report. 58 The seeded growth protocol used for S-OPE 7 - b -PNIPAM 22 was utilized for D-OPE 7 - b -PNIPAM 22 , given the structural similarity between S-OPE 7 and D-OPE 7 . The appearance of the wider and darker central block flanked by one or two gray ends indicated that segmented diblock and triblock comicelles were formed from the seeds of S-OPE 9 - b -P2VP 56 with a width of 23 nm as indicated by purple arrows in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The length of the resulting comicelles appeared to increase linearly with n unimer / n seed , which was shown in our previous report. 58 The seeded growth protocol used for S-OPE 7 - b -PNIPAM 22 was utilized for D-OPE 7 - b -PNIPAM 22 , given the structural similarity between S-OPE 7 and D-OPE 7 . The appearance of the wider and darker central block flanked by one or two gray ends indicated that segmented diblock and triblock comicelles were formed from the seeds of S-OPE 9 - b -P2VP 56 with a width of 23 nm as indicated by purple arrows in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…π-Conjugated core-forming OPE 7 with an alkyne chain end with a molecular weight of 2187 g mol −1 was first prepared by the iterative Sonogashira coupling reaction, followed by chain end modification according to our previous reports. 46,47 Corona-forming PNIPAM chains of different lengths were prepared by atom transfer radical polymerization (ATRP) from azide-containing initiators. 47 Subsequently, OPE 7 - b -PNIPAM n ( n = 8, 22 and 47) BCPs with low polydispersities ( M w / M n ≤ 1.18) were obtained by Cu-catalyzed alkyne/azide cycloaddition reactions (Scheme 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the propensity for most conjugated polymer building blocks to exhibit strong π–π interactions and crystallize easily, living CDSA presents a promising avenue for the diverse conjugated BCPs. Specifically, various conjugated core-forming blocks have been reported, including P3HT, , poly­(di- n -hexylfluorene) (PDHF), , poly­(3-decylselenophene) (P3DSe), oligo­( p -phenylene­ethynylene) (OPE), , and oligo­( p -phenylene­vinylene) (OPV), ,, which have been the focus of numerous studies aimed at controlling the nanostructures using living CDSA techniques.…”
Section: Crystallization-driven Assembly Of Conjugated Bcpsmentioning
confidence: 99%